Improving the Quality of Venous Blood Sampling Procedure (Phlebotomy): Avoiding Tourniquet Use - Freitas, Francisco; Alves, Mónica (Journal of Laboratory Physicians, 2021)
Background Phlebotomy guidelines discourage tourniquet use whenever possible. We assessed phlebotomists' capability of not using the tourniquet in venous blood sampling, hypothesizing it to be equal to 50% of the patients attended, and identifying the most frequent venipuncture site.Materials and Methods We assigned two phlebotomists of the same age (41 years) and experience (20 years) to record 10 phlebotomy days, the first with prioritized and the latter with nonprioritized patients. Each acquired daily data for the number of attended patients, age, gender, frequency of nontourniquet usage, and punctured vein. To test our work hypothesis we used the two-tailed single sample t-test. Differences between age-group means and nontourniquet use means by each phlebotomist were tested by two-tailed t-test for independent means.Results In 10 phlebotomy days, 683 patients were attended (males 43.2%). We found no statistically significant difference between age-group means. The combined capability of nontourniquet use was 50.5%, which did not differ from our null hypothesis, but the difference in individual group means was statistically significant, the means being 33% and 66.9% (prioritized vs. nonprioritized). The medial cubital vein was the most prone to be punctured (77.7%).Conclusion Performing phlebotomies without tourniquet was possible in at least half of the attended patients, though it was more limited in specific group populations.
Keywords: tourniquet application; phlebotomy; venous blood sampling; guidelines; preanalytical phase; quality improvement